The Racine Belles: The Rise and Fall of the Stars of the All- American Girls Professional Baseball League - Dupont, Jacqueline E. (My University, 2010)
This thesis will survey the rise and fall of the Racine Belles, an All-American Girls Professional Baseball team that was created to save professional baseball during the 1940s and 1950s. During this time, Major League Baseball's leading players joined the war effort to combat the Axis powers during the Second World War, creating a fear that the loss of these men could lead to the end of the sport. This thesis questions why the popular and victorious Belles were disbanded sooner than other AAGPBL teams. This triumphant event in women's history and the effects of the Racine Belles and other AAGPBL teams' success on the future of women's sports still lingers. The research for this paper consisted of studying multiple secondary sources such as historical monographs and scholarly journals. More importantly, the research includes the use of primary sources from the National Baseball Hall of Fame and Museum.
Keywords: Racine Belles (Baseball team); All-American Girls Professional Baseball League--History; Baseball for women--Wisconsin--History; Baseball--Wisconsin--Racine--History; Women baseball players--History